A Review on Post-Harvesting Losses and Opportunities in Cold Chain - Pendhari, Asiya S; SN Husainy, Avesahemad; S Balikai, Swaranjali; Yadav, Rahul A; M Shaikh, Mashkur; J Nagarji, Aftab (Journal of Advanced Research in Mechanical Engineering and Technology, 2021)
The food supply chain is one of the most complex systems. The system begins with production and then continues with food handling techniques for preservation. In practice, the surplus food distributed seems to have been passing through various stages before it actually reaches out to consumers. However, the question arises if all the food produced is totally consumed. In this paper, we shall be studying the distinct stages involved in the food supply chain; how and where the food loss takes place; and the tremendous impacts it caused socially and economically. This paper will further help in quantifying the food waste and shall be obliged in identifying the required actions to overcome food loss and waste globally. This paper outlines different strategies and approaches adopted for post-harvest food loss assessments in order to achieve sustainable food services; move towards zero waste economy to implement poverty extermination and food security around the world. How to cite this article: Husainy ASN, Pendhari AS, Balikai SS et al. A Review on Post-Harvesting Losses and Opportunities in Cold Chain. J Adv Res Mech Engi Tech 2020; 7(4): 1-7. DOI: https://doi.org/10.24321/2454.8650.202007